Revision of the semi-empirical mass formula coefficients by using the ame2020 database - Sara Gjorgievska, Hristijan Kochankovski, Koviljka Stankovic, Lambe Barandovski (ScienceDirect, 2024)
This work aims to revise the coefficients of the Bethe-Weizsäcker’s Semi-empirical mass formula by using the latest version release of the Atomic Mass Evaluation Database (AME2020). The updated values of five energy term coefficients are determined based on the binding energy of a total of 2548 nuclei from AME2020 database. Least-squares fitting is used to obtain a new set of mass formula coefficients. The results obtained are in good agreement with the experimental AME2020 data in a wide range of the nuclei binding energy. The relative error, with respect to the experimental data does not exceed 1%, which is less than the oscillations obtained in the other works using earlier database version AME2016 due to the more accurate measurements and the larger data sample. The semi-empirical mass formula provides a good approximation of the atomic masses and thereby, with the refined coefficient values given here, other effects in the nuclear fission engineering can be calculated with higher accuracy.